Down-converted photon pairs in a high-Q silicon nitride microresonator - Bohan Li; Zhiquan Yuan; James Williams; Warren Jin; Adrian Beckert; Tian Xie; Joel Guo; Avi Feshali; Mario Paniccia; Andrei Faraon; John Bowers; Alireza Marandi; et al. (Nature, 2025)
Abstract Entangled photon pairs from spontaneous parametric down-conversion (SPDC)1 are central to many quantum applications2–6. SPDC is typically performed in non-centrosymmetric systems7 with an inherent second-order nonlinearity (χ (2))8–10. We demonstrate strong narrowband SPDC with an on-chip rate of 0.8 million pairs per second in Si3N4. Si3N4 is the pre-eminent material for photonic integration and also exhibits the lowest waveguide loss (which is essential for integrated quantum circuits). However, being amorphous, silicon nitride lacks an intrinsic χ (2), which limits its role in photonic quantum devices. We enabled SPDC in Si3N4 by combining strong light-field enhancement inside a high optical Q-factor microcavity with an optically induced space-charge field. We present narrowband photon pairs with a high spectral brightness. The quantum nature of the down-converted photon pairs is verified through coincidence measurements. This light source, based on Si3N4 integrated photonics technology, unlocks new avenues for quantum systems on a chip.